2022
DOI: 10.3390/jcm11113114
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cancer and BRCA Mutations: A Systematic Review

Abstract: This systematic review identifies, evaluates, and summarises the findings of all relevant individual studies on the prevalence of BRCA mutation (BRCAm) in endometrial cancer patients and the incidence of endometrial cancer in BRCAm women patients. Consequently, the benefits and limits of a prophylactic hysterectomy at the time of the risk-reducing salpingo-oophorectomy are analysed and discussed. A systematic literature search was performed in the databases of PubMed, Cochrane, and Web of Science until May 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Among breast cancer survivors (not screened for germline mutations), increased risks of developing uterine or ovarian cancer higher than 150% and 40%, respectively, have been observed compared to the general population [ 64 ]. A recent review found that BRCA mutations were identified in 4.3% of women with endometrial cancer [ 65 ]. Moreover, a genomic mutation study that evaluated BRCA-associated mutational and transcriptomic profiles demonstrated the prognostic role of BRCA pathogenetic variants in patients affected by endometrial carcinoma, reporting lower levels of immune cell infiltration, higher expression of immunosuppressive checkpoint molecules, and worse prognoses in the presence of BRCA-associated mutations compared with wild-type BRCA [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among breast cancer survivors (not screened for germline mutations), increased risks of developing uterine or ovarian cancer higher than 150% and 40%, respectively, have been observed compared to the general population [ 64 ]. A recent review found that BRCA mutations were identified in 4.3% of women with endometrial cancer [ 65 ]. Moreover, a genomic mutation study that evaluated BRCA-associated mutational and transcriptomic profiles demonstrated the prognostic role of BRCA pathogenetic variants in patients affected by endometrial carcinoma, reporting lower levels of immune cell infiltration, higher expression of immunosuppressive checkpoint molecules, and worse prognoses in the presence of BRCA-associated mutations compared with wild-type BRCA [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same differences were confirmed in an independent Australian cohort [ 97 ]. A recent systematic review did not provide strong evidence in favor of performing a routine hysterectomy at the time of the risk-reducing surgery [ 65 ], but these conclusions should be revised after the publication of new evidence [ 67 , 69 , 70 , 72 ]. Undoubtedly, prophylactic hysterectomy, due to its costs and potential complications (bleeding, infection, organ lesions, and vaginal cuff dehiscence), should be individually balanced with the potential increased risk of uterine cancer in this population.…”
Section: Resultsmentioning
confidence: 99%
“…Across EC histologies and molecular subgroups, common genomic events have the potential to produce HRD. Germline pathogenic variants in HRR genes, including BRCA 1/2 , BRIP1 , and RAD51C , have been reported in EC 11–15 . A systematic review identified gBRCA1/2 pathogenic variants in up to 4.3% of ECs 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Germline pathogenic variants in HRR genes, including BRCA1/2, BRIP1, and RAD51C, have been reported in EC. [11][12][13][14][15] A systematic review identified gBRCA1/2 pathogenic variants in up to 4.3% of ECs. 12 Molecular profiles (NGS600) from 1475 ECs demonstrated pathogenic variants in HRR genes in 34.4% of cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation